JERAT HUKUM KEBIRI PELAKU KORBAN KEKERASAN SEKSUAL PADA ANAK - Vience Ratna Multiwijaya; Ermania Widjajanti (LPPM STIH Awang Long, 2023)
In Indonesia, sexual violence against children has increased. The criminal sanctions contained in the Child Protection Act do not reduce child sexual violence. In 2016, the Government issued Law Number 17 of 2016 which aims to reduce the level of child sexual violence by imposing aggravating punishment on perpetrators, such as announcing the identity of the perpetrators, as well as administering chemical castration and installing electronic detection devices. The chemical castration sanction is an action sanction that must be accompanied by rehabilitation after the perpetrator has carried out the principal sentence regulated in Government Regulation No. 70 of 2020. Implementation must be based on a Court Decision which has permanent legal force and with a maximum period of 2 years after going through the stages of examination. In principle, chemical castration is an act of injecting anti-testosterone substances into a man's body to reduce levels of the hormone testosterone. Carrying out castration is often misunderstood, it is not throwing away the testicles, but chemical injections are carried out. Administering this anti-androgen drug can make men deficient in the hormone testosterone so that they no longer have sexual desire. Castration is considered a violation of human rights, according to Article 28 G paragraph (2) of the 1945 Constitution of the Republic of Indonesia. The negative effects of chemical castration can cause premature aging and bone loss or osteoporosis The research method uses a normative juridical approach using legislation. The implementation of chemical castration needs attention to see if it can answer the reduction of sexual violence. This must be adapted to the criminal objective of fostering or improving the perpetrators, not just suffering in retaliation, but punishment must be for the welfare of society and protection for victims.